MRI signs of intracranial hypertension in morbidly obese and normal-weight individuals - Schmill, Lars-Patrick Andreas; Peters, Sönke; Juhász, Julia; Jansen, Olav; Laudes, Matthias; Aludin, Schekeb (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Purpose Idiopathic intracranial hypertension (IIH) is associated with intracranial abnormalities, although not obligatory, which can be detected with cranial MRI. Obesity is an important risk factor for IIH and a pathogenetic link is suspected but the extent to which these MRI signs are already related to obesity has not yet been examined. We investigated whether IIH-MRI signs are present more often in obese individuals with a BMI > 30 kg/m² than in individuals of normal weight.Materials and Methods Brain MRI of 32 obese and 53 normal-weight participants from the Food-Chain-Plus cohort were analyzed for three main signs of IIH: (I) stenosis of the transverse sinus, (II) increased width of the optic nerve sheath, and (III) reduction of pituitary height. In addition, a scoring system for the MRI signs was applied. Furthermore, tortuosity of the optic nerve and flattening of the posterior globe were considered as additional MRI signs.Results Obese participants had a significantly higher MRI score (p < 0.001) than those in the normal-weight cohort, with significant differences in quantitative measurements of cerebral venous sinus stenosis (p < 0.001), widening of the optic nerve sheath (p < 0.05), and flattening of the pituitary gland (p < 0.05) also always being observed more frequently and in a more pronounced manner in the obese group. Furthermore, our findings correlated significantly with BMI and proportionately with hip and waist circumference.Conclusion Obese individuals show a significantly higher prevalence of cerebral MRI signs related to IIH. This supports the hypothesis that obesity is a risk factor for possible intracranial hypertension and reinforces the suspicion that obesity is involved in the pathomechanism of IIH.Key points:
Keywords: MR-imaging; hypertension; metabolic Disorders